Innovative Aqueous Nanoemulsion Prepared by Phase Inversion Emulsification with Exceptional Homogeneity - Patrícia C. Pires; Mariana Fernandes; Francisca Nina; Francisco Gama; Maria F. Gomes; Lina E. Rodrigues; Sara Meirinho; Samuel Silvestre; Gilberto Alves; Adriana O. Santos (MDPI AG, 2023)
Formulating low-solubility or low-permeability drugs is a challenge, particularly with the low administration volumes required in intranasal drug delivery. Nanoemulsions (NE) can solve both issues, but their production and physical stability can be challenging, particularly when a high proportion of lipids is necessary. Hence, the aim of the present work was to develop a NE with good solubilization capacity for lipophilic drugs like simvastatin and able to promote the absorption of drugs with low permeability like fosphenytoin. Compositions with high proportion of two lipids were screened and characterized. Surprisingly, one of the compositions did not require high energy methods for high droplet size homogeneity. To better understand formulation factors important for this feature, several related compositions were evaluated, and their relative cytotoxicity was screened. Optimized compositions contained a high proportion of propylene glycol monocaprylate NF, formed very homogenous NE using a low-energy phase inversion method, solubilized simvastatin at high drug strength, and promoted a faster intranasal absorption of the hydrophilic prodrug fosphenytoin. Hence, a new highly homogeneous NE obtained by a simple low-energy method was successfully developed, which is a potential alternative for industrial application for the solubilization and protection of lipophilic actives, as well as (co-)administration of hydrophilic molecules.